2019
DOI: 10.1055/s-0039-1692721
|View full text |Cite
|
Sign up to set email alerts
|

Linking Complement Activation, Coagulation, and Neutrophils in Transplant-Associated Thrombotic Microangiopathy

Abstract: Transplant-associated thrombotic microangiopathy (TA-TMA) is a severe and life-threatening complication of hematopoietic cell transplantation (HCT) that often coincides with graft-versus-host-disease (GVHD). Although endothelial damage seems to be the common denominator for both disorders, the role of complement system, neutrophils, and coagulation has not been clarified. In an effort to distinguish the pathogenesis of TA-TMA from GVHD, we evaluated markers of complement activation, neutrophil extracellular tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 48 publications
5
40
0
2
Order By: Relevance
“…Furthermore, our group has also proposed a cutoff value for distinguishing complement activation in TA-TMA from GVHD by the degree of complement activation. 15 In line with our previous findings, the present study confirms for the first time that EASIX is associated with sC5b-9.…”
supporting
confidence: 93%
“…Furthermore, our group has also proposed a cutoff value for distinguishing complement activation in TA-TMA from GVHD by the degree of complement activation. 15 In line with our previous findings, the present study confirms for the first time that EASIX is associated with sC5b-9.…”
supporting
confidence: 93%
“…These changes are similar to those previously observed in TA-TMA [11,12]. Similar to TA-TMA [13], complement also seems to play a role in GVHD-associated organ injury following alloHCT [14,15]. In a recent study, Ma et al [16] have also confirmed that complement is involved in renal damage following alloHCT.…”
supporting
confidence: 82%
“…Taking into account previous experience from other coronaviruses, several recent studies have implicated complement activation as part of the vicious cycle of endothelial dysfunction in COVID-19 [ 37 ]. Complement is a major regulator of endothelial injury syndromes, such as thrombotic microangiopathies [ 38 , 39 ]. Severe COVID-19 appears to resemble complement-mediated thrombotic microangiopathies in both pathophysiology and clinical phenotype [ 40 ].…”
Section: Introductionmentioning
confidence: 99%